COMPOSITE PEDAGOGICAL STAFF-CLUSTERS AS A CONDITION OF DEPARTMENT EDUCATIONAL AND METHODICAL WORK DEVELOPMENT - Vladimir A. Fedorov; Aleksandr V. Stepanov; Tatyana M. Stepanova (Obrazovanie i Nauka)
The aim of the investigation is to justify urgency and efficiency of teachers’ collective work of the chair on formation of integrated special professional competences of trainees.Methods. Teamwork is considered as a leading method of aim realisation; it is suggested to carry this method in practice on the basis of a situational technique of intra-chair structure formation – composite staff-clusters, whose activity is based on synergetic interaction of educational process participants.Results. Described innovations will give the chance to carry out necessary integration of educational processes content; will promote natural interaction of teachers on the basis of the generated complete integrated subsystem – composite staff-clusters. The innovation vector can be connected with more dimensional field of integration, i.e. generating not only special professional competences, but also general professional and common cultural ones.Scientific novelty. Activity of pedagogical composite staff-clusters is offered to consider in the complete block of scientific-theoretical and practice-pedagogical aspects: scientifically-organizational, academic, practice-organizational, educational, etc. Scientific novelty of article is connected with expansion of some content positions which are based on scientific-theoretical conclusions of researches pedagogic-collective (by V. A. Suhomlinsky, etc.) and organizational-psychological (by K. Rogers, etc.) processes, and also ideas of synergetics extrapolated into organizational-pedagogical processes. It is shown that efficiency of educational process can be reached under a condition of organizational and methodical work interrelatedness; synthesis of administrative and performing activity on the basis of the whole educational process interaction. Necessity of composite pedagogical creativity is proved by synergetic processes and motivation-emotional characteristics.Practical significance. Authors give specific proposals concerning actual problems solution in higher school: problem overcoming of “disciplinary step-type behaviour” of chair work, a stereotype of “formal interdisciplinary interaction” by re-structuring of chairs on a scientific basis of staff creativity. The authors suggest that creation of similar new (innovative) pedagogical working conditions of high school chairs is necessary in the nearest future. Such organisation will give the chance to carry out real communication of a science with practice and as a whole will raise quality and productivity of educational processes in higher educational institutions.